Analisis Kebutuhan Pengembangan Multimedia Interaktif BANTAR pada Pembelajaran Bangun Datar Siswa Sekolah Dasar - Riza Fatchur Rochim; Kharisma Eka Putri; Sulistiono Sulistiono (YASIN, 2026)
Mathematics learning on plane figure material in elementary schools still faces challenges in helping students understand abstract concepts, particularly because of the limitations of learning media that still depend on surrounding objects and lecture methods. This study aims to analyze the need for developing BANTAR interactive multimedia on plane figure material for fourth-grade students at SDN Tiron 4 Kediri. This study used a descriptive qualitative approach with data collection techniques through interviews and questionnaires. The research subjects consisted of 28 fourth-grade students, while the questionnaire instrument used a Guttman scale with Yes and No response options. The results showed that 80% of students had difficulty understanding plane figure material, 80% of students found it easier to understand the material when mathematics learning used learning media, and 90% of students were interested in learning using interactive multimedia. These findings indicate a strong need for the development of BANTAR interactive multimedia as a more engaging and interactive mathematics learning medium. The conclusion of this study affirms that the development of BANTAR interactive multimedia is needed to support students’ understanding of plane figure concepts in accordance with the learning characteristics of elementary school students. The implications of this study provide a basis for developing interactive multimedia-based mathematics learning media that are relevant to students’ needs and the elementary school learning context.